Asymptotic Periodicity for Strongly Damped Wave Equations - Claudio Cuevas; Carlos Lizama; Herme Soto (Abstract and Applied Analysis)
This work deals with the existence and uniqueness of asymptotically almost-periodic mild solutions for a class of strongly damped semilinear wave equations.